2021
DOI: 10.1007/s00035-021-00260-z
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground-trait variations in 11 (sub)alpine plants along a 1000-m elevation gradient in tropical Mexico

Abstract: With the aim to explore how plants acclimate to elevation changes in the understudied (sub)alpine tropics we tested two hypotheses along a 1000-m elevation gradient in Mexico: (H1) due to a severe increase in abiotic constraints at higher elevations, the functional traits of the plant species will converge toward more resource conservation, and (H2) the specific growth forms and biogeographic origins present in the (sub)alpine tropics may influence the interspecific trait variation along the gradient. We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…Whereas root trait patterns were highly idiosyncratic between elevations, leaf traits generally varied as hypothesized, with plants having lower SLA and denser and thicker leaves at higher elevations. Similar and largely consistent intraspecific relationships between leaf traits and elevation were also observed for the majority of species by Cruz-Maldonado et al, (2021) and Kichenin et al, (2013). Albert et al, (2010) however, reported more diverse intraspecific leaf trait patterns across 15 species along a 300 -1000 m gradient in the French Alps.…”
Section: Within Species Leaf Traits Varied More Consistently Than Roo...supporting
confidence: 69%
See 1 more Smart Citation
“…Whereas root trait patterns were highly idiosyncratic between elevations, leaf traits generally varied as hypothesized, with plants having lower SLA and denser and thicker leaves at higher elevations. Similar and largely consistent intraspecific relationships between leaf traits and elevation were also observed for the majority of species by Cruz-Maldonado et al, (2021) and Kichenin et al, (2013). Albert et al, (2010) however, reported more diverse intraspecific leaf trait patterns across 15 species along a 300 -1000 m gradient in the French Alps.…”
Section: Within Species Leaf Traits Varied More Consistently Than Roo...supporting
confidence: 69%
“…Collected plants (herbaceous species) or branches (woody species) with leaves attached were stored cooled in moist plastic bags during the field work and were rehydrated overnight in water at 4°C until further analysis (Cruz-Maldonado et al 2021). Within 24 h of collection in the field, we selected between 5 and 25 healthy, fully expanded leaves without petioles from each individual.…”
Section: Trait Measurementsmentioning
confidence: 99%
“…The observed pattern of selection for increased height at flowering in B. stricta, a highly selfing plant, is likely not mediated by pollinators. Instead, we propose that the genetic cline of declining height with elevation in this and other studies (Gairola et al, 2008;Wadgymar et al, 2017a;Cruz-Maldonado et al, 2021) is driven by strong selection for early reproduction at high-elevation locations associated with short growing seasons and genetic trade-offs between height and timing of flowering (Bemmels and Anderson, 2019). We did not manipulate the length of the growing season or vary conditions temporally across the season and thus cannot directly evaluate how these agents of selection influence trait evolution.…”
Section: Size At Floweringmentioning
confidence: 70%
“…Given the gradual change in species and growth form diversity as elevation increases, we expected changes in growth form diversity. For example, we expected an increase in graminoid and shrub species because their growth form might be more resilient to changes in microclimatic conditions or, in the case of shrubs, higher temperatures result in favorable conditions for them (Harte and Shaw, 1995;Cruz-Maldonado et al, 2021;Lasso et al, 2021). While there has not been a clear trend for AGB under warming conditions, we expected an increase in AGB due to the previously mentioned increase in shrubs and graminoids that may contribute more biomass per square meter than other growth forms.…”
Section: Introductionmentioning
confidence: 90%